2019
DOI: 10.1155/2019/4625279
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Effect of Lycopene and Dark Chocolate on Gut Microbiome with Systemic Changes in Liver Metabolism, Skeletal Muscles and Skin in Moderately Obese Persons

Abstract: Lycopene rich food and dark chocolate are among the best-documented products with a broad health benefit. This study explored the systemic effect of lycopene and dark chocolate (DC) on gut microbiota, blood, liver metabolism, skeletal muscle tissue oxygenation and skin. 30 volunteers were recruited for this trial, 15 women and 15 men with a mean age of 55 ± 5.7 years and with moderate obesity, 30 < BMI < 35 kg/m2. They were randomized and divided into five equal interventional groups: three received diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(81 citation statements)
references
References 47 publications
1
58
0
2
Order By: Relevance
“…Furthermore, there was a significant change in certain butyrate-producing microbes (Faecalibacterium, Ruminococcus, and Oscillospira). These results indicate that prebiotic consumption reinforces microbial diversity and has beneficial effects on the health of the host (Wiese et al, 2019).…”
Section: Probiotics and Prebiotics Effect On Obesity And Weight Gainmentioning
confidence: 65%
See 2 more Smart Citations
“…Furthermore, there was a significant change in certain butyrate-producing microbes (Faecalibacterium, Ruminococcus, and Oscillospira). These results indicate that prebiotic consumption reinforces microbial diversity and has beneficial effects on the health of the host (Wiese et al, 2019).…”
Section: Probiotics and Prebiotics Effect On Obesity And Weight Gainmentioning
confidence: 65%
“…Probiotics may also inhibit fat accumulation, reduce inflammation and insulin resistance, and regulate neuropeptides and gastrointestinal peptides (Sivamaruthi et al, 2019;Wang et al, 2019b). Prebiotics: Traditionally, prebiotics were considered to be non-metabolized food ingredients, which reach the intestinal lumen and are selectively utilized by beneficial microbes in the host (Tandon et al, 2019;Wiese et al, 2019). Inulin, galacto-oligosaccharides (GOS), and fructo-oligosaccharides (FOS) are the most frequently analysed prebiotic supplements in recent studies (Wiese et al, 2019).…”
Section: Probiotics and Prebiotics Effect On Obesity And Weight Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, EC supplementation (20 mg/kg BW) did not restore high fat diet-induced changes in mouse microbiota profiles [22]. In terms of PAC, a recent study showed that consumption of dark chocolate (70% cocoa) by obese individuals increases the relative abundance of Lactobacillus, which might have anti-obesity effects [49]. PACs also exert bacteriostatic effects in humans, that might contribute to the modulation of microbiota composition [50].…”
Section: Ec and The Gastrointestinal Tractmentioning
confidence: 98%
“…Além da atividade antioxidante, outras funções podem ser desempenhadas pelo licopeno. Em um estudo randomizado, onde 30 voluntários com obesidade moderada receberam doses de licopeno de 7 mg/dia e 30 mg/dia, foi observada uma modulação na microbiota intestinal com abundância de Bifidobacterium adolescentis e B. longum, evidenciando, de forma inédita, a sua ação prebiótica (Wiese et al, 2019). Research, Society and Development, v. 9, n. 10, e3469108094, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8094 elaboração de filmes plásticos, em especial em embalagens ativas e inteligentes para alimentos com alto teor lipídico.…”
Section: Licopenounclassified